Relevance and success of IS teaching and research: An analysis of the "Relevance Debate" - Carola Schauer (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2007)
This report is part of a series of publications on the status and development of the North-American Information Systems (IS) field and Wirtschaftsinformatik (WI), its counterpart in German speaking countries. Information systems in businesses and organizations are the main subject of research in IS and WI. Hence, both disciplines are applied fields of research. Thus, the valuation of research results and graduates by business practice are vital indicators for the disciplines' status and success. Between 1991 and 2001 a plethora of articles were published in leading Information Systems (IS) journals and conference proceedings addressing the issue of relevance of IS research and teaching. This research report provides a comprehensive conten analysis of this relevance debate in the North-American Information Systems field. The perceptions, opinions, and recommendations of the contributors are presented structured according to statements of valuation, perception, explanation, and recommendation. The reconstruction of the main IS relevance debate indicates that all debate participants agree that relevance to practice plays a vital role for the IS discipline, but that the field largely lacks relevance in terms of research as well as in terms of teaching. The lack of relevance is, for example, illustrated by the general perception that research results rarely impact practice and that IT/IS professionals usually do not read academic IS journals. In order to analyse if the debate has lead to any changes in terms of practice relevance of the IS field the most recent literature and studies available on IS relevance are evaluated. Analysis results indicate that no significant changes took place. But various IS researchers still report on problems in terms of acceptance and perception of IS degree programs and research. Based on the perspectives of experienced researchers from WI and other European IS communities the concluding remarks of this report attempt to explain the apparent lack of change in the North-American IS field and provide suggestions for improving the current status of the IS field in terms of relevance.
Keywords: 650